ANALISIS KOMPARATIF TENTANG ZHALIM DALAM AL-QUR’AN (TAFSIR AL-MARAGHI DAN TAFSIR AL-MISBAH) - Istiqomah, Novita Nissa; Ridho, Muhammad Mukharom; Astuti, Indri (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Abstarct The objective of this study is to examine and compare the interpretations of verses related to zulm in Tafsir Al-Maraghi and Tafsir Al-Misbah by M. Quraish Shihab, as well as how these interpretations can be applied in daily life. Given that Tafsir Al-Maraghi is one of the monumental works of Qur'anic exegesis in the modern era, it holds significant relevance for this research. On the other hand, Tafsir Al-Misbah offers a contemporary interpretation of the Qur'an presented in an accessible and contextual style. This study explores the similarities and differences in how both scholars understand the concept of zulm in the Qur'anic discourse, employing a comparative approach and library research methodology. The findings indicate that zulm is perceived as both a spiritual and social phenomenon that disrupts individual and communal harmony. These interpretations are highly relevant in addressing contemporary social issues, such as the negative impact of social media on social cohesion and spiritual well-being. This research not only enriches academic discourse on Qur'anic exegesis but also offers practical insights for Muslims on how to embody Islamic values in daily life through virtuous behavior, meaningful living, and the promotion of social justice in modern society. Keywords: Tafsir Al-Maraghi, Tafsir Al-Misbah, Zulm, Social Justice, Qur’anic exegesis.